Intratumoral stromal morphometry predicts disease recurrence but not response to 5‐fluorouracil—results from the QUASAR trial of colorectal cancer. Issue 3 (27th November 2017) - Hutchins, Gordon G A; Treanor, Darren; Wright, Alexander; Handley, Kelly; Magill, Laura; Tinkler‐Hundal, Emma; Southward, Katie; Seymour, Matthew; Kerr, David; Gray, Richard; Quirke, Philip; ,
Abstract : Aims: The biological importance of tumour‐associated stroma is becoming increasingly apparent, but its clinical utility remains ill‐defined. For stage II/Dukes B colorectal cancer (CRC), clinical biomarkers are urgently required to direct therapeutic options. We report here prognostic/predictive analyses, and molecular associations, of stromal morphometric quantification in the Quick and Simple and Reliable (QUASAR) trial of CRC. Methods and results: Relative proportions of tumour epithelium (PoT) or stroma (PoS) were morphometrically quantified on digitised haematoxylin and eosin (H&E) sections derived from 1800 patients enrolled in QUASAR, which randomised 3239 (91% stage II) CRC patients between adjuvant fluorouracil/folinic acid (FUFA) chemotherapy and observation. The prognostic and predictive values of PoT/PoS measurements were determined by the use of stratified log‐rank analyses. A high proportion of tumour stroma (≥50%) was associated with an increased recurrence risk: 31.3% (143/457) recurrence for ≥50% versus 21.9% (294/1343) for <50% [rate ratio (RR) 1.62; 95% confidence interval (CI) 1.30–2.02; P < 0.0001]. Of patients with stromal proportions of ≥65%, 40% (46/115) had recurrent disease within 10 years. The adverse prognostic effect of a high stromal proportion was independent of established prognostic variables, and was maintained in stage II/Dukes B patients (RR 1.62; 95% CI 1.26–2.08; P = 0.0002). KRAS mutation in the presence of a high stromal proportion augmented recurrence risk (RR 2.93; 95% CI 1.87–4.59; P = 0.0005). Stromal morphometry did not predict response to FUFA chemotherapy. Conclusions: Simple digital morphometry applied to a single representative H&E section identifies CRC patients with a >50% higher risk of disease recurrence. This technique can reliably partition patients into subpopulations with different risks of tumour recurrence in a simple and cost‐effective manner. Further prospective validation is warranted.